Opioid Use Disorders Are Associated With Perioperative Morbidity and Mortality in the Hip Fracture Population. Issue 5 (May 2018) - Summers, Spencer; Grau, Luis; Massel, Dustin; Rosas, Samuel; Ong, Alvin; Hernandez, Victor Hugo
Abstract : Objectives: To determine whether opioid use disorders (OUDs) are associated with adverse perioperative outcomes in patients undergoing surgical fixation for proximal femur fractures. Methods: The National Hospital Discharge Survey was queried to identify patients surgically treated for proximal femur fractures between 1990 and 2007. Patients were grouped into those with a diagnosis of OUD, nonopioid drug use disorder, or neither. Demographic information and comorbidities were included in univariable and multivariable analyses to identify independent risk factors for perioperative outcomes. Results: A total of 8154 patients with a diagnosis of drug use disorder and 4704 patients with a diagnosis of OUD were identified from a cohort of 4, 732, 165 surgically treated proximal femur fractures. Patients with OUD were significantly younger (46 vs. 79), and a significantly smaller proportion of them had medical comorbidities (21.9% vs. 60.2%) when compared with the no drug misuse cohort. Patients with OUD had significantly more medical complications (51.1% vs. 26.8%), mechanical complications (3% vs. 0.3%), and adverse events (55% vs. 39.7%) when compared with the no drug misuse group. OUD had higher odds for leaving against medical advice [odds ratio (OR) 12.868, range 10.7771–15.375], for any adverse event (OR 4.107, range 3.869–4.360), and for mortality (OR 1.744, range 1.250–2.433) when compared with nondrug misusers. Conclusions: Despite being younger and with significantly less medical comorbidities, patients with OUD have higher odds for adverse events, leaving against medical advice, and mortality after surgical treatment of a hip fracture. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.